Бесы: роман в 3 частях / Ф. М. Достоевский - Достоевский Федор Михайлович (Удмуртия, 1990)
Экземпляры: ф.3 (1991) / Инвентарный номер: 33178 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Д 70 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44